Transformational Leadership and Burnout in Bank Negara Indonesia Pontianak: Thriving as Mediating Role and Employees' Openness to Experience as Moderating Role - Virginia, Cecilia Silky B1024161015 (Jurnal Manajemen Update, 2020)
TRANSFORMATIONAL LEADERSHIP AND BURNOUT IN BANK NEGARA INDONESIA PONTIANAK: THRIVING AS MEDIATING ROLE AND EMPLOYEESâ€™ OPENNESS TO EXPERIENCE AS MODERATING ROLE By: Cecilia Silky Virginia ABSTRACT The main goal of every business is to gain profit and business growth. Especially in banking industry, gaining more customers and serve the best to maintaining customers are the priorities. While the employees are expected to work for the company and achieving the goals stated, itâ€™s not closed the possibility of stress in work, and also employees could feel the exhaustion and tired-ness along the way in a working place. The employees that feel under-appreciated and exhausted tends to have a low performance and impacting the business. The purpose of this research is to analyze the relationship of Transformational Leadership and Burnout in Bank Negara Indonesia Pontianak, with employee thriving as mediating role and moderating role by employeesâ€™ openness to experience. The research has been conducted in all branches of Bank Negara Indonesia Pontianak. Banking industry as one of the strictest industry with high target of business. Transformational Leader and employeeâ€™s burnout has been studied for a huge amount of study. In addition, thriving and openness to experience as positive attitude and characteristics from the employees. This research is a survey research that is conducted to understand the causal relationships between variables with the use of questionnaire as the instrument to obtain data. The questionnaire consist of sample which is obtained through distribution to 110 respondents who fulfill the requirements. The sample of this research is front â€“ liner employees in Bank Negara Indonesia with at least 6 months of experience and non â€“ internship nor outsourcing. In this research, the data analysis method used is Structural Equation Model Partial Least Square (SEMPLS) method. To conduct analysis using PLS method, this research is using smartPLS 3.0 software. The hypotheses of the research are H1: Transformational Leadership is positively related to employee thriving is supported, H2: Thriving is negatively related to employeeâ€™s burnout is supported, H4: Openness to Experience moderates the positive relationship between Transformational Leadership and thriving such that this relationship is stronger when Openness to Experience is high compared to low is supported, while H3: Thriving mediates the negative effect of Transformational Leadership on employee burnout is not supported. Keywords: transformational leadership, burnout, thriving, openness to experienceReferencesÂ Al-Amin, M. (2017). Transformational leadership and employee performance: mediating effect of employee engagement.Antonakis, J., Avolio, B., & Sivasubramaniam, N. (2003). Context and Leadership: An Examination of the Nine-Factor Full-Range Leadership Theory Using the Multifactor Leadership Questionnaire.Arnold, K., & Connelly, C. (2013). Transformational Leadership and Psychological Wellâ€being.Avolio, B. J., & Bass, B. M. (2004). Multifactor Leadership Questionnaire. Manual and Sampler Set (3rd ed.). Redwood City, CA.Avolio, B., Bass, B., & Jung, D. (1999). Re-examining the components of transformational and transactional leadership using the Multifactor Leadership Questionnaire. Journal of Occupational and Organizational Psychology, 72, 441ÃŽ462. DOI: 10.1348/096317999166789.Bass, B. (1985). From transactional to transformational leadership: Learning to share the vision, Volume 8, Issue 3, p. 19-31.Bass, B. (1990). Leadership and performance beyond expectations. New York, NY: Free Press.Bass, B., & Avolio, B. (1995). MLQ Multifactor leadership questionnaire. Redwood City, CA. Mind Garden.Bass, B., & Riggio, R. (Psychology Press, 2006). Transformational Leadership.Brummelhuis, L., & Bakker, A. (2012). A resource perspective on the work-home interface: the work-home resources model.Burns, J. M. (1978). Leadership. Harper & Row. New York.Campbell, D., & Fiske, D. (1959). Convergent and discriminant validation by the multitrait-multimethod matrix. Psychological Bulletin, 56(2), 81-105.Cavazotte, F., Moreno, V., & Bernardo, J. (2013). BAR - Brazilian Administration Review.Conger, J., & Kanungo, R. (1987). Toward a Behavioral Theory of Charismatic Leadership in Organizational Settings.Costa, P. T., & McCrae, R. R. (1992). Four ways the five factors are basic. Personality and Individual Differences, 13, 653-665. DOI: 10.1016/0191-8869(92)90236-I.Costa, P., & McCrae, R. (1992). Normal personality assessment in clinical practice: The NEO Personality Inventory.Dafler, F. (2013, April 23). Terindah. Retrieved from Memahami dan Mempelajari SmartPLS: http://feroniadafler.blogspot.co.id/2013/04/mempelajari-dan-memahami-smartpls.htmlDaud, I., & Afifa, N. (2019). Pengaruh Gaya Kepemimpinan Transformasional dan Komitmen Organisasional terhadap Prestasi Kerja Pegawai pada PDAM Tirta Khatulistiwa Pontianak.Dechawatanapaisal, D. (2017). Employee retention: the effects of internal branding and brand attitudes in sales organizations. Personnel Review, Vol. 47 Issue: 3, 675 - 693.Demerouti, E., Bakker, A., Nachreiner, F., & Schaufeli, W. (2003). The Job Demandsâ€“Resources Model of Burnout. Journal of Applied Psychology 86(3):499-512 Â·.Den Hartog, D., Miujen, V. V., & Koopman, P. (1997). Transactional versus transformational leadership: An analysis of the MLQ. Journal of Occupational and Organizational Psychology.Dionne, S. (2004). Transformational leadership and team performance.Fielder, F. (1964). A Contingency Model of Leadership Effectiveness. Advances in Experimental Social Psychology.Freundenberger, H. (1974). Staff Burnâ€Out.Garcia-Rivera, B., Mendoza-Martinez, I., & Ramirez-Baron, M. (2013). The Impact of Transformational Leadership in Burnout.Ghozali, I. (2008). SEM Metode Alternatif dengan PLS.Goldberg, L. R. (1999). A broad-bandwidth, public domain, personality inventory measuring the lower-level facets of several five-factor models. In I. Mervielde, I. Deary, F. De Fruyt, & F. Ostendorf (Eds.),. Personality Psychology in Europe, Vol. 7.Halbesleben, J. (2006). Sources of social support and burnout: A meta-analytic test of the conservation of resources model. Journal of Applied Psychology, 91(5), 1134-1145.Halbesleben, J. R., Neveu, J.-P., Paustian-Underdahl, S. C., & Westman, M. (2014). Getting to the "COR": understanding the role of reesource in conservation of resources theory. JOurnal of Management 40, 1334-1364. DOI: 10.1177/014920631452713.Heffner, C. L. (2016). Test Validity and Reliability. Retrieved from AllPsych: http://allpsych.com/researchmethods/validityreliability/Hildenbrand, K., Sacramento, C., & Binnewais, C. (2018). Transformational Leadership and Burnout: The Role of Thriving and Followers Openness to Experience.Hobfoll, S. (1989). Conservation of resources. A new attempt at conceptualizing stress.Hobfoll, S. (2001). The influence of culture, community, and the nested-self in the stress process: Advancing conservation of resources theory. Applied Psychology: An International Review, 50, 337ÃŽ421. DOI: 10.1111/1464-0597.00062 .Hox, J. J., & Bechger, T. (2011). An Introduction to Structural Equation Modeling. Family Science Review, 354-373.Ismail, M., Kasim, M. I., Amit, M., & Razdi, R. (2009). Roles, Attitudes, and Competencies of Managers of CSR-Implementing Companies in.Iverson, R. D., Olekalns, M., & Erwin, P. J. (1998). Affectivity, organizational stressors, and absenteeism: A causal model of burnout and its consequences. Journal of Vocational Behavior, 52, 1-23. DOI:10.1006/jvbe.1996.1556.Kogut, B., & Zander, U. (1993). Knowledge of the firm and the evolutionary theory of the multinational corporation.Komariah, A., & Satori, D. (2010). Metodologi Penelitian Kualitatif. Bandung: Alfabeta.Langelaan, S., Bakker, A. B., Van Doornen, L. J., & Schaufeli, W. B. (2006). Burnout and work engagement: Do individual differences make a difference? Personality and Individual Differences 40, 521-532. DOI: 10.1016/j.paid.2005.07.009.Lengnick-Hall, Cardy, R. L., & Mark, L. (2011). Will They Stay or Will They Go? Exploring a Customer-Oriented Approach To Employee Retention. Journl of Business and Psychology, 26(2), 213-217.Malhotra, N. (2010). Introduction: Analyzing Accumulated Knowledge and Influencing future Research. Review of Marketing Research ISBN: 978-0-85724-475-8, eISBN: 978-0-85724-476-5.McCrae, R. R. (1987). Creativity, divergent thinking, and openness to experience. Journal of Personality and Social Psychology, 52(6), 1258-1265. http://dx.doi.org/10.1037/0022-3514.52.6.1258.Merriam-Webster. (2018). Merriam-Webster: Questionnaire. Retrieved from Merriam-Webster:: https://www.merriam-webster.com/dictionary/questionnaireNielsen, K., & Daniels, K. (2012). Does shared and differentiate leadership predict followers working condition and well-being? The Leadership Quarterly, 23, 383-397.Northouse, P. (2013). Leadership: Theory and Practice, 6th Edition.Ã–zÃ§elik, G. (2015). Engagement and Retention of the Millennial Generation in the Workplace through Internal Branding. International Journal of Business and Management; Vol. 10, No. 3; .Parveen, M., & Adeinat, I. (2019). Transformational leadership: does it really decrease work-related stress? Leadership & Organization Development Journal, Vol. 40 No. 8, pp. 860-876. https://doi.org/10.1108/LODJ-01-2019-0023.Paterson, T., Luthans, F., & Jeung, W. (2013). Thriving at work: Impact of psychological capital and supervisor support.Piccolo, R. F., & Colquitt, J. A. (2006). Transformational leadership and job behaviors: The mediating role of core job characteristics. Academy of Management Journal, 49, 327ÃŽ340. DOI: 10.5465/AMJ.2006.20786079.Porath, C., Spreitzer, G., Gibson, C., & Garnett, F. G. (2012). Thriving at work: Toward its measurement, construct validation, and theoretical refinement. Journal of Organizational Behavior 33(2): 250-275.Preacher, K. J., Rucker, D. D., & Hayes, A. F. (2007). Addressing moderated mediation hypotheses: Theory, methods, and prescriptions. Multivariate Behavioral Research, 42, 185 227. DOI: 10.1080/00273170701341316.Richsen, H. (2015). Validity. Retrieved from Linguistic: http://linguistics.byu.edu/faculty/henrichsenl/ResearchMethods/RM_2_18.htmlSmith, P., & Peterson, M. (1988). Leadership, Organizations and Culture. London.Spreitzer, G. M., Sutcliffe, K., Dutton, J. E., Sonenshein, S., & Grant, A. M. (2005). A socially embedded model of thriving at work. Organization Science, 16, 537ÃŽ550. DOI 10.1287/orsc.1050.0153.TechTarget. (2018). Definition: Hypothesis. Retrieved from TechTarget: https://whatis.techtarget.com/definition/hypothesisWeber, A., & Jackel-Reinhard, A. (2000). Burnout syndrome: a disease of modern societies?Westerman, J. W., & Yamamura, J. H. (2007). Generational preferences for work environment fit: effects on employee outcomes. Career Development International, Vol. 12 Issue: 2, 150-161.Wikipedia. (2015). Convergent Validity. Retrieved from Wikipedia: https://en.wikipedia.org/wiki/Convergent_validityWikipedia. (2016). Wikipedia. Retrieved from Discriminant Validity: https://en.wikipedia.org/wiki/Discriminant_validityWilliams, C. (2007). Research Methods. Journal of Business & Economics Research.Xu, S., Jiang, X., & Walsh, J. (2016). The influence of openness to experience on percieved employee creativity: The moderating roles of Individual trust.